PROBLEMS ABOUT THE ENGLISH LANGUAGE FOR PROFESSIONAL PURPOSES IN A NON-LINGUISTIC UNIVERSITY - Kushakov, Yusup (Журнал иностранных языков и лингвистики, 2023)
English for Special Purposes is the main component of language learning in the preparation of qualified specialists in various fields. There is a lot of literature on this subject various studies are being carried out, special teaching methods in this area, but, unfortunately, most of the research is carried out by foreign scientists. Graduates today the requirement is a qualified specialist with knowledge of a foreign language. The author highlights the key points in this sphere.